S36 The adhesion receptor CADM1 promotes human mast cell viability. (2nd December 2011) - Moiseeva, E P; Leyland, M L; Bradding, P
Abstract : Introduction and Objectives: Cell adhesion molecule 1 (CADM1) contributes to cell–cell adhesion, proliferation and adhesion-induced degranulation in human lung mast cells. Previously we found that it is expressed as three alternatively spliced isoforms (major SP4 and SP1, and minor SP6) in human lung mast cells (HLMCs) and only SP4 in the cell line HMC-1, originating from mast cell leukaemia. Here we investigated the role of CADM1 in the viability of HLMCs and HMC-1. Methods: Modulation of CADM1 expression was investigated using adenoviral delivery in both HMC-1 and HLMCs. Cell viability in the absence of survival factors was determined by measuring cell numbers and caspase-3/7 activity. Results: Modulation of CADM1 expression in HMC-1 cells and HLMCs by overexpressing SP4 (exon 8/11) and SP1 (exon 8/9/11) and RNA interference was confirmed by FACS and Western blotting. Overexpression of SP4 did not affect HMC-1 viability (105%±7% of original number of cells) or caspase-3/7 activity (7.7±0.2 FU/cell) in IMDM only for 48 h vs GFP-transduced cells, but overexpression of SP1 reduced cell number (66%±1%) and increased caspase-3/7 activity (9.8±0.3 FU/cell). CADM1 knockdown reduced HMC-1 number (71%±2%) and increased caspase-3/7 activity (9.5±0.2 FU/cell) in these conditions. In contrast to HMC-1 cells, overexpression of SP4 in HLMCs enhanced cell survival (39%±3%) in IMDM alone after 72 h compared to non-transduced cells (31%±1%, whereas downregulation of CADM1 reduced cell number to 26%±2%. Caspase3/7 activity was increased in HLMCs with downregulated CADM1 (99±20 FU/cell) compared to SP4-overexpressing and non-transduced cells (40±4 FU/cell and 20±1 FU/cell respectively). HLMCs displayed lower basal levels of Mcl-1, parallelled with lower survival and higher caspase-3/7 activation compared to HMC-1 cells. CADM1 downregulation in HLMCs coincided with decreased basal expression of Kit and Mcl-1. Conclusions: Modulation of CADM1 isoform expression or CADM1 downregulation in HMC-1 cells reduced survival. Conversely, SP4-overexpression or CADM1 downregulation in HLMCs resulted in increased survival or increased cell death, respectively. CADM1 modulation in HLMCs coincided with modulation of proteins related to survival. Hence, CADM1 promotes survival in human mast cells.